MODELS OF THE PROJECT MANAGEMENT SYSTEM OF DEVELOPMENT OF THE ELECTROENERGETIC COMPLEX - Левыкин, Виктор Макарович; Кудрявцева, Марина Сергеевна; Садовский, Артур Александрович (Eastern-European Journal of Enterprise Technologies, 2012)
In this article a target and functional models of the project management system of development of the electroenergetic complex are offered that allowing to describe targets and management functions of the system taking into account their decomposition for achievement of the global purpose.